Investigation on the Synthesis and Photocatalytic Property of Uranyl Complexes of the β-Diketonates Biscatecholamide Ligand - Qingchun Zhang; Bo Jin; Rufang Peng; Xiaofang Wang; Zhaotao Shi; Qiangqiang Liu; Shan Lei; Hua Liang (International Journal of Photoenergy)
A series of uranyl complexes have been synthesized by reacting hexadentate ligands CH2[COO (CH2)nCAM; n=2, 3, 4]2 [CAM = 2,3-Ph(OH)2CONH] containing the catecholamide (CAM) group and β-diketonates framework with uranyl nitrate. They were characterized by FTIR, UV-vis, 1H NMR, XPS, TGA, and elemental analysis. The analysis revealed that oxygen atom of β-diketonate did not bind to uranyl ion in complexes 1–3. The photocatalytic degradation properties of the target complexes for degradation of rhodamine B (RhB) were investigated. The result indicated that approximately 74%, 71%, and 67% RhB were degraded in the presence of complexes 1–3 after about 210 min, respectively. Consequently, complexes 1–3 have excellent photocatalytic degradation property.